Evaluation Report on Three Years Working of Artificial Insemination Scheme at Bakshi-Ka-Tulab, Lucknow - Planning Commission (Planning Commission, 1958)
The Artificial Insemination Centre at Bakshi-ka-Talab was started in October, 1952. This centre had a good start in the beginning for the first six months, but thereafter, the progress of its working showed a gradual decline. In July, 1955, the additional Development Commissioner, U.P., visited this A. I. Centre and after examining records of its performance, he desired that Dr. Rama Das, the then Officer Incharge, Training Centre, Bakshi-ka-Talab, should make a comprehensive investigation so as to throw light on the problems which were hindering the progress of A. I. work of this centre and to suggest ways and means to improve its working. Shortly after this, the Deputy Director, Animal Husbandry, Lucknow Circle, visited the centre and stressed the necessity of improving the working of the centre.
Planning Research and Action Institute, Planning Department, Uttar Pradesh